Energy End-use and Grid Interaction Analysis of Solar Assisted Ground Source Heat Pumps in Northern Canada. (June 2016) - Kegel, Martin; Wong, Steven; Tamasauskas, Justin; Sunye, Roberto
Abstract: This paper presents an analysis conducted on a ground source heat pump (GSHP) system coupled with evacuated tube solar thermal collectors to reduce the borefield size in Northern Canada. The annual energy consumption, utility costs, grid impact, greenhouse gas emissions, and economics of a solar assisted GSHP system are compared to several conventional and heat pump (HP) space heating, cooling and domestic hot water systems for mid-rise apartment buildings located in Whitehorse, YK and Yellowknife, NT. In both regions the solar assisted GSHP system demonstrated energy savings over a conventional space heating system, while successfully overcoming an annual ground energy imbalance and reducing the required borefield size. From a grid perspective, although the HP systems shifted the space heating fuel source from fuel oil to electricity, the solar thermal system is able to help minimize the use of inefficient auxiliary heat to meet the space heating loads. The high associated capital costs of a GSHP system coupled with a solar thermal system make the economics difficult to justify; however for regions where energy security is of high importance, the energy savings achieved with these systems can have a substantial impact.